Implementasi Kampanye Sosial Program Vaksinasi di Indonesia Sebagai Bentuk Pemulihan Pasca-Pandemi Covid-19 - Hasna, Sofia (Tuturlogi: Journal of Southeast Asian Communication, 2023)
The Pandemic Covid-19 in Indonesia continues with an increase in cases counting until January 28, 2021, there were 13,695 cases with a total of 1,037,993 cases of Covid-19 since it was first announced in early March 2020, therefore there is a need for post-pandemic-recovery-efforts-Covid-19-vaccination-program as a form of herd immunity carried out through campaigns on social media with the hashtag #VaksinCovid19. So that the communication element becomes very important in persuading the public to carry out a social campaign for the Covid-19 vaccination program as a form of post-pandemic recovery. This research aims to see how the implementation of post-pandemic Covid-19 recovery through a social campaign for the vaccination program. This research method uses descriptive qualitative with a literature study method that comes from secondary sources. The Result shows that the current government needs an appropriate communication strategy and target targets based on demographics to the psychology of the community, besides that, it also requires stakeholders to expand engagement in the social campaign for the Covid-19 vaccination program. Also, referring to secondary data with the Brand24 application to see the effectiveness of #VaksinCovid19 shows that the public perception of the Covid-19 vaccine program campaign is still classified as negative.